2019
DOI: 10.1177/0263395719885753
|View full text |Cite
|
Sign up to set email alerts
|

Judicial public relations: Determinants of press release publication by constitutional courts

Abstract: It remains unclear what institutional characteristics determine the publication of press releases by constitutional courts. Research has revealed that courts use press releases to disseminate information; however, little is known about when exactly courts choose to publish a press release on a ruling. By focusing on institutional elements, this study argues that press releases form a part of judicial public relations and are used to enhance openness and transparency surrounding specific court rulings. This arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…These aspects have motivated constitutional assemblies to adapt or mirror the institutional design of the German court when establishing judicial review, as it was shown for the newly established courts in post-communist countries (Hönnige 2007 ; Holtz-Bacha 2017 ) as well as for judiciaries in Latin America (Navia and Ríos-Figueroa 2005 ). Finally, the FCC’s public relations approach shares central aspects with several other highest courts’ communication strategies worldwide (Davis and Taras 2017 ; Meyer 2020 , 2021 a, b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These aspects have motivated constitutional assemblies to adapt or mirror the institutional design of the German court when establishing judicial review, as it was shown for the newly established courts in post-communist countries (Hönnige 2007 ; Holtz-Bacha 2017 ) as well as for judiciaries in Latin America (Navia and Ríos-Figueroa 2005 ). Finally, the FCC’s public relations approach shares central aspects with several other highest courts’ communication strategies worldwide (Davis and Taras 2017 ; Meyer 2020 , 2021 a, b).…”
Section: Methodsmentioning
confidence: 99%
“…The meeting reports analysed in this study are written and published by the court’s public relations office, headed by a trained judge, who is selected for a two to three year period by the FCC’s president (Meyer 2020 ). The public relations office was established in 1996 in the wake of an institutional crisis caused by mishandled communication of two significant cases (Schaal 2015 ; Holtz-Bacha 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schließlich könne die starke Übernahme auch mit den antizipierten Medienlogiken durch die Pressestelle der Staatsanwaltschaft erklärt werden, die in ihren Mitteilungen vor allem solche Fälle und Fallmerkmale berichten, die für JournalistInnen potenziell von Interesse sein könnten. Dass diese Erwägungen tatsächlich eine Rolle bei der juristischen Medienarbeit spielen können, zeigt auch ein Befund von Meyer (2019), der in seiner Studie analysierte, welche Faktoren den Versand von Medienmitteilungen (Publikation Medienmitteilung ja/nein) durch Gerichte selbst determinieren. Er stellt fest, dass vor allem Gerichtsurteile, die einen vorhergehenden niedrig-instanzlichen Entscheid korrigieren oder Status Quo-Änderungen bedeuten und damit den Nachrichtenfaktor Konflikt bzw.…”
unclassified